3: Vitamin D Improves Autologous Fat Graft Retention. (July 2021) - Leftwich, Patricia A.; Lee, Phoebe L.; Loder, Shawn; Nerone, Wayne; Marra, Kacey; Peter Rubin, J.; Kokai, Lauren E.
Abstract : Purpose: Autologous fat grafting is a widely used technique in aesthetic and reconstructive surgery, however, unpredictable volume reabsorption may lead to unsatisfactory outcomes. Previously, we demonstrated that a fat-soluble Vitamin D3 analogue, calcitriol, significantly improved fat retention in a xenograft mouse model by 25% across multiple donors when injected systemically (p < 0.05). While calcitriol has minimal toxicity, is FDA approved, and has positive immunomodulatory and antioxidant properties, systemic administration bypasses key Vitamin D synthesis regulatory steps, thus increasing risk with high-dose use. We hypothesize that systemic supplementation with Vitamin D3 (cholecalciferol) will likewise improve fat-graft retention similar to calcitriol while avoiding potential regulatory and iatrogenic risk. In this study we compared in vivo human fat graft retention in mice treated with systemic cholecalciferol, calcitriol or vehicle control in a mouse xenograft model. In vitro adipose lipoaspirate culture was used to interrogate the therapeutic mechanism of action. Methods: Lipoaspirate was harvested from 6 unique donors using a 2mm cannula and used in parallel for both in vitro and in vivo studies. In vivo: 0.3mL of lipoaspirate was injected bilaterally on dorsal flanks of homozygous Foxn1nu immunocompromised mice. Calcitriol (50ng), cholecalciferol (50ng, 500ng, 5000ng) or vehicle control was administered thrice weekly by IP injection. Graft volume retention was measured at 12 weeks. In vitro: 1mL of lipoaspirate was submerged in phenol-red free DMEM (10% FBS) containing calcitriol or cholecalciferol (15.6nM, 62.5 nM or 250 nM) for 7 days with one media change. Terminal analyses include tissue weight, stromal cell viability, concentration of active vitamin D metabolite (1, 25(OH)2D3), and gene upregulation by qRT-PCR. Results: Previously, we demonstrated that systemic administration of 50ng calcitriol thrice weekly significantly improved human fat graft retention across multiple donors in a mouse xenograft model. Our current in vivo data suggest 5000ng cholecalciferol is similarly effective. In-vitro assays show 62.5nM and 250nM cholecalciferol significantly increased adipose stromal cell viability compared to controls (85.3+/-2.9% and 87.7+/-3.7 versus 77.6+/-2.8%, respectively p<0.05;). Analysis of final adipose 1, 25(OH)2D3 concentration by ELISA showed both calcitriol and cholecalciferol treatments equally increased Vitamin D metabolite concentrations in all donors. qRT-PCR analysis of gene expression show that pro-survival autophagy is significantly increased by both cholecalciferol and calcitriol, though increased concentration of calcitriol was required to induce significant increases from controls. Conclusion: Cholecalciferol (Vitamin D3) is a highly promising therapeutic for improving fat grafting outcomes. Our in vitro data suggests that in the context of hypoxia, nutrient depletion, or growth factor deprivation, such as occurs immediately following fat grafting, vitamin D3 promotes stromal cell autophagy. In this context, autophagy is crucial for maintaining cellular ATP production and macromolecular synthesis and, therefore, represents an essential pro-survival pathway which allows grafted cells to survive. The results herein provide evidence to incorporate vitamin D3 as a safe, cost-effective nutritional supplement into the perioperative workflow to improve fat viability after grafting.